MENINGKATKAN HASIL BELAJAR IPA MELALUI METODE DEMONSTRASI - Nur, Iriani (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
Learning in SD Negeri Seuneubok Pidie, East Aceh Regency, especially class V on science subjects about material for breathing instruments in humans and animals, mastery of material is still very low or has not been successful. Of the 21 students, only 5 students (24%) achieved the Minimum Completion Criteria (KKM) which was set at 6.5 with an average score of 57.4. To overcome the above problems, the steps that need to be implemented are using the Demonstration Method. In its application, the researcher tried on the science subject about the concept of